Embracing Pluriversalism in Knowledge Production and Dissemination: Towards the Ethical Imperative to Listen to "Worlds and Knowledges Otherwise" - Sugiharto, Setiono (Jurnal Arbitrer, 2024)
The fetish for disseminating knowledge through scholarly publication is tangible today with local scholars being heavily pressured to publish in both indexed local and international journals. While this intellectual endeavour is commendable for knowledge generation and dissemination, the very notion of knowledge is still strongly influenced by the Euro-and Western-centric orientation. This article problematizes the perpetuation of such knowledge especially in local academic publishing (i.e. Indonesia), and invites local scholars to mull over the possibility for thinking and acting otherwise, for seeking a radical alternative out of the existing alternatives, and for considering other ways of knowing and of being – that is to say, to embrace pluriversalim of knowledge through a space of “worlds and knowledges otherwise” (Escobar, 2007). In so doing, we can cultivate among local scholars another way of thinking – non-Euro-and non-Western-modes of thinking. The article will first examine the long-held scientific tradition in local academic writing and publishing practices. Then it discusses the lingering processes of intellectual hegemony in these practices. Finally, it offers another radical thought for creating a space of worlds and knowledges otherwise.